Virtual Prototyping of a Low-Height Lifting System for Offshore Wind Turbine Installation - Xu, Jiafeng; Ataei, Behfar; Halse, Karl Henning; Hildre, Hans Petter; mikalsen, egil tennfjord (Volume 9: Ocean Renewable Energy, 2020)
Due to the ever higher demands from the energy market, the quantity, dimension and power capacity of newly installed offshore wind turbines are continuously increasing. In terms of logistical management, economic feasibility and engineering difficulty, the traditional installation methods, predominantly represented by using Jack-up vessel and offshore cranes, will hit their limitations soon in the future. Offshore turbines have a relatively fixed geometric profile and physical characteristics: a slender cylindrical tower with huge blades attached on the top end. In this work, we exploited these features and designed a low-height lifting system for deploying wind turbine onto a floating spar platform. The low-height lifting system lifts the wind turbine with wires attached to the bottom of the tower, and keeps the balance of the tower with extra tug lines on the mid-section. The wires and tug lines are controlled by an active 6DOF compensation system. The low-height lifting system removes the necessity of a huge offshore crane onboard and can scale well to even larger wind turbines. The design is virtual prototyped in the simulator of Offshore Simulator Centre using FATHOM simulation software. Different design configurations are discussed in terms of the general arrangement, system dimensions and control methods. publishedVersion Locked until 18.6.2021 due to copyright restrictions. Copyright © 2020 by ASME